PAESAGGIO E URBAN FOOD PLANNING - Giacomo Pettenati (Bollettino della Società Geografica Italiana, 2019)
Landscape, both as visible features of places and as set of cultural and identity values, should be considered as a crucial element of food systems. The aim of this paper is to explore the presence of this concept in the debate about food systems and urban food planning. In the first part of the paper, three main perspectives on food landscapes are presented: food systems as producers of landscape, foodscapes as frameworks for any food-related action and food landscapes as heritage. The second part explores urban food landscapes, focusing on landscapes of urban agriculture, on the role of consumers as co-producers of landscape and on urban foodscapes as resources for new urban images strategies of urban development. In the third part, the presence of landscape as field of action in existing Urban Food Strategies/Policies is investigated, showing its underrepresentation. The conclusions discuss the potential role of landscape in urban food policies both as the object of specific strategies or actions and as a useful conceptual framework, able to connect the actors of the food system, in sharing a vision for its future evolution.